2002
DOI: 10.1645/0022-3395(2002)088[0411:sotgia]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Toxoplasma gondii Infection Among Two Mountain Aboriginal Populations and Southeast Asian Laborers in Taiwan

Abstract: A seroepidemiological survey of Toxoplasma gondii infection among Atayal and Paiwan mountain aborigines and Southeast Asian laborers in Taiwan was assessed from February 1998 to July 2000 using a latex agglutination test. To determine risk factors for T. gondii infection among Taiwan aborigines, the consumption of raw meat and valley water were given particular attention in a self-administered questionnaire. The overall seroprevalence of T. gondii infection was 19.4% for Atayal, 26.7% for Paiwan, 42.9% for Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 6 publications
1
10
1
Order By: Relevance
“…Compared with neighboring countries, the overall seroprevalence in the present study was similar to that reported in Japan (10.3z) (13), and in Changchun, northern China Toxoplasma in Pregnant Women in Taipei City (10.6z) (16); however, the overall seroprevalence in the present study was higher than that reported in South Korea (4z) (12). The difference in seroprevalence among pregnant women in different districts may be attributable to the habits of aboriginal Taiwanese populations of consuming raw liver or other meat products from pigs and rats, as well as to their low economic status, leading to increased risks of infection with toxoplasmosis (22,24,25); however, immigrant pregnant women may be susceptible to toxoplasmosis because of poor hygiene habits associated with their low socioeconomic status, resulting in a high seroprevalence (22). Nevertheless, immigrant pregnant women may have been infected before they came to Taiwan and should not be ignored.…”
Section: Discussioncontrasting
confidence: 56%
“…Compared with neighboring countries, the overall seroprevalence in the present study was similar to that reported in Japan (10.3z) (13), and in Changchun, northern China Toxoplasma in Pregnant Women in Taipei City (10.6z) (16); however, the overall seroprevalence in the present study was higher than that reported in South Korea (4z) (12). The difference in seroprevalence among pregnant women in different districts may be attributable to the habits of aboriginal Taiwanese populations of consuming raw liver or other meat products from pigs and rats, as well as to their low economic status, leading to increased risks of infection with toxoplasmosis (22,24,25); however, immigrant pregnant women may be susceptible to toxoplasmosis because of poor hygiene habits associated with their low socioeconomic status, resulting in a high seroprevalence (22). Nevertheless, immigrant pregnant women may have been infected before they came to Taiwan and should not be ignored.…”
Section: Discussioncontrasting
confidence: 56%
“…15 However, other studies among Taiwan indigenous people have reported a lower seroprevalence of 19.4% to 21.8% in Atayal, 16 26.7% in Paiwan, 17 and 9.1% in Akka 17 subgroups. In contrast, seroprevalence rates among indigenous people in Brazil 18 and Venezuela [19][20][21][22][23] have been relatively high: 73.5% and up to 88.0%, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…Most clinical laboratories therefore utilize serological tests such as latex agglutination (LA) test, enzyme-linked immunosorbent assay, and indirect fluorescent antibody test to detect antibodies against T. gondii in infected individuals. The LA test has been widely used in remote areas of developing countries because of its high specificity and sensitivity as well as convenience (8)(9)(10)(11)(12)(13)(14). Serological surveys of T. gondii infection have been conducted in several regions; however, seroprevalence rates vary between investigations.…”
Section: Introductionmentioning
confidence: 99%